Application of a Knowledge, Attitude, Belief, and Practice Model in Pain Management of Patients with Acute Traumatic Fractures and Alcohol Dependence - Ying Dong; Hui Gao; Zheyu Jin; Jue Zhu; Hao Yu; Yingqing Jiang; Jun Zou (Pain Research and Management)
Objective. To evaluate the outcome of a knowledge, attitude, belief, and practice mode (KABP) in the pain management in patients with acute traumatic fractures complicated with alcohol dependence. Methods. Twenty-nine alcohol-dependent male patients with acute traumatic fractures and who received surgical treatment between January 2019 and December 2020 were included in this retrospective case-control study. The age range was 30–65 years (average 50.03 ± 7.94). Fracture Type. Six cases of spinal burst fractures and 23 cases of limb trauma fractures. Ten patients were treated with routine nursing (control group), and 19 patients were treated with pain management in KABP mode (experimental group). The control group received traditional pain care, including the conventional numerical rating scale (NRS) pain score system, with focus on symptomatic treatment. On this basis, the experimental group managed pain using KABP, including cognitive behavioral intervention, optimization programs, modification of personal beliefs, and behavior patterns. NRS, self-rated anxiety/depression scale (SAS), and quality of life (SF-36) scale were applied at admission, 1 day before surgery, and 3 months after surgery. Results. The perioperative NRS score of the KABP group was lower than that of the control group, and the postoperative anxiety levels improved. Discharge satisfaction was significantly higher than that in the control group (p<0.05). There were behaviors promoting health in the experimental group, and five patients expressed abstinence behavior after discharge (p<0.05). Conclusion. Patients with alcohol dependence represents a unique set of cases for perioperative pain management. To ensure patient safety, individualized pain management through the application of KABP can significantly reduce postoperative pain and promote the generation of healthy behaviors in patients.